The Effect Of Company Size, Liquidity and Leverage On Environmental Costs With Foreign Ownership As Moderating Variable - Pratama, Muhammad Rahmadi; Heniwati, Elok; Yunita, Khristina; Dosinta, Nina Febriana; Damayanti, Fera (STMIK Widya Cipta Dharma, 2025)
Environmental damage caused by business entities activity causes negative impact to society, especially mining companies that have many environmental cases such as Timah, Vale and several other large mining companies. With high funding capabilities, these large companies can easily fund environmental contributions, but the reality on the ground is the opposite, raising questions about what hinders or encourages companies in deciding to invest in the environment. The aim of this research is to understand the relationship between company size, liquidity and leverage on environmental costs moderated by foreign ownership. The population of this research is mining companies registered on IDX for the 2021-2023 period by using purposive sampling technique as a way to select samples. There are 31 companies and 93 data in the sample. This research uses secondary data in the form of annual reports and sustainability reports. Eviews 13 is used as a tool in conducting analysis and uses multiple linear regression analysis techniques and moderated regression analysis. The results conclude that company size has no significant effect on environmental costs while foreign ownership does not moderate the relationship between company size, liquidity and leverage on environmental costs. On the other hand, liquidity and leverage have a significant negative effect on environmental costs. This research has implications for academics by providing new understanding and authority as a consideration in making regulations.